A linguistic landscape analysis of shop signs - Wahyu Mubarak; Kismullah Abdul Muthalib (English Education Journal, 2021)
It is surprising to find that there have been many shops in Banda Aceh that use English on their signs. This study was conducted to investigate the shop owners’ reasons for using English on their shop signs. To obtain the data from the shop owners, observation sheet and interview guide were used as the research instruments. The data were analyzed by using the model proposed by Miles, Huberman, and Saldana (2014). It was found that the 10 shop owners gave four reasons they used English in their shop signs, which can be classified into the themes. They are 1) to be easily remembered; 2) to follow the trend; 3) to use their own name; and 4) to be unique. In conclusion, among four terms of reasons of shop owners in using English in their shop signs, the theme of “becoming unique” or distinctive is the most given reason by the shop owners.